A Pragmacognitive Approach to the Study of some Internet Scientific Articles: Headline Titles - Mª Isabel González Pueyo; Alicia Redrado Lacarta (Miscelánea: A Journal of English and American Studies, 2003)
The proliferation of new media and electronics modes of communication in public life, and the recent increase in the interdisciplinary nature of academic and professional discourse, has brought about an increasing appropriation of lexicogrammatical resources and rhetorical strategies across discourse communities and genres. Thus, new forms or hybrid forms of cybergenres are now under discussion. This paper argues that scientific and technical articles undergo an accommodation process in response to the medium and the assumed tenets of the internet audience. As these modifications can be best embodied in the titles, which display significant pragmalinguistic and generic information, this paper focus on analysing some of the titles encountered at a random choice in the personal homepages to observe, first, how the blurring of alien genres begins at this outstanding discursive space. Then, titles shall provide the analyst with significant insights into the angle of telling, and hence the traits technoscientists are eager to reveal about themselves. It is argued that this is the result of marketing criteria, which attempting to enhance the writer’s self-advertisement and the digital medium, often give undue representation to the needs and interests of web users. The methodology and discussion of this paper follows a pragma-cognitive approach of genre theory, text typology, and systemic functional analysis.